Epidemiologic evidence of slow growing, nonprogressive or regressive breast cancer: A systematic review. Issue 3 (15th April 2016) - Segnan, Nereo; Minozzi, Silvia; Armaroli, Paola; Cinquini, Michela; Bellisario, Cristina; González‐Lorenzo, Marien; Gianola, Silvia; Ponti, Antonio
Abstract : The general aim of this systematic review is to mitigate breast cancer (BC) overdiagnosis and overtreatment. The specific aim is to summarize available data on the occurrence and features of indolent invasive or in situ (DCIS) BC, and precisely survival of untreated cases, prevalence of occult cancers found in autopsies, frequency of regressive BC. PubMed, Embase and Cochrane Library were systematically searched up to 3/31/2014. Eligibility criteria were: cohort studies, case‐control studies, uncontrolled case series assessing survival in women with a diagnosis of BC who did not receive treatment compared to treated women; case series of autopsies estimating the prevalence of undiagnosed BC; cohort studies, case‐control studies, uncontrolled case series, case reports assessing the occurrence of spontaneous regression of BC in women with a confirmed histology diagnosis. Untreated BC: 8 cohort studies and 12 case series (3593 BC) were included. In three controlled cohort studies (diagnoses 1978–2006), the 5‐years overall survival was 19–43%. Occult BC: 8 case series (2279 autopsies) were included. The prevalence of invasive BC undiagnosed during lifetime range was 0–1.5%, while for DCIS the range was 0.2–14.7%. Spontaneous regression: 2 cohort studies, 3 case reports, 1 case series included. In the cohort studies the relative risk of regression for screen detected compared with nonscreened BC was estimated as 1.2 and 1.1. It seems plausible that around 10% of invasive BC are not symptomatic during life, and that one fith of BC patients if untreated would be alive after 5 years. Around 1 of 10 screen‐detected BC may regress according two studies. Abstract : What's new? The advance of breast cancer (BC) care depends heavily on mitigating overdiagnosis and overtreatment. However, reaching that goal requires greater understanding of the natural history of BC, including the occurrence and features of slowly developing breast tumors. Here, a summary of data from the literature on regressing or not progressing BCs suggests that numerous clinically insignificant ductal lesions are included among ductal carcinoma in situ BCs. Furthermore, about 10% of invasive BCs remain asymptomatic during life, being detected only on autopsy, and about 20% of patients, left untreated, would survive five years after diagnosis.